Pycnodysostosis at otorhinolaryngology. (April 2017) - Baglam, Tekin; Binnetoglu, Adem; Fatih Topuz, Muhammet; Baş Ikizoglu, Nilay; Ersu, Refika; Turan, Serap; Sarı, Murat
Abstract: Aim: Pycnodysostosis is a rare autosomal, recessive, skeletal dysplasia caused by a mutation in the cathepsin k gene. Pycnodysostosis is characterized by short stature, characteristic facial appearance (delayed closure of fontanelles and cranial sutures, mandibular hypoplasia and angle disorder, blue sclera), and acroosteolysis of the distal phalanges. Our aim was to describe the otorhinolaryngologic findings, differential diagnoses, various treatment options, and followup in eight cases of pycnodysostosis. Method: This retrospective clinical study used data from eight patients diagnosed with pycnodysostosis by a single pediatric endocrinologist primarily based on clinical and radiographic findings. All patients were referred to the otorhinolaryngology outpatient clinic by the pediatric endocrinology unit of the Marmara University between February 2013 and March 2015. Detailed medical histories were obtained in all cases and otorhinolaryngologic physical examination, blood assays, electrocardiogram, lateral skull X-rays, chest radiograph, cephalometric investigations, tympanograms, and audiograms were also carried out. Sleep videos of patients were recorded and those with upper airway problems were evaluated for sleep apnea by polysomnography. Informed consent form was obtained from the parents of all patients. Results: Eight patients (7 females and 1 male) displaying proportionate dwarfism were included in the study. They had a mean age of 14.7 years (range: 13–16 y), the mean height of 141.3 cm (range 132–155 cm), and mean weight of 44.4 kg (range: 39.6–49.3 kg). All patients had facial dysmorphism with frontal bossing and the hands and feet had short digits with overlying cutaneous wrinkles that tapered off with large overriding nails. Midfacial hypoplasia and malocclusion were observed in seven of the eight patients (87.5%), four (50%) had micrognathia, and five (62.5%) had proptosis. Tympanograms and audiograms of all patients were type A and normal, and the mean of the pure tone audiogram was 13.3 dB (range: 10–16 dB). All patients had a narrow and grooved palate with disturbed dentition; two of them (25%) had mild markedness of the tongue base, five (62.5%) had grade 3 and three (37.5%) had grade 2 tonsillar hypertrophy, and five (62.5%) had adenoid hypertrophy. One patient (12.5%) had grade 3 Mallampati, four (50%) showed grade 2 Mallampati while three (37.5%) patients displayed grade 1 Mallampati score. Further, while six (75%) patients had no uvular pathology, one (12.5%) patient presented with uvular elongation and another patient had a bifid uvula. Cephalometric measurements such as PAS-UP (mean 5.67 mm; range: 5.0–7.6 mm) and PAS-TP (mean 9.61 mm; range: 8.5–12.2 mm) were lower than that of normal subjects. Video recordings showed that six of the eight patients (75%) had respiratory distress and four (50%) had sleep apnea. Polysomnography in these patients with sleep apnea showed that two had mild OSA (AHI: 18.2 and 20.1 events/hour) and two had severe OSA (AHI: 53.4 and 62.8 events/hour). For upper airway problems, an adenotonsillectomy was performed in two (25%) patients while two others required an adenoidectomy. Positive pressure ventilation was recommended in two patients with persistent sleep apnea after adeno/adenotonsillectomy. However, because of the parental objections, the follow-up polysomnographs could not be obtained. Conclusion: Pycnodysostosis is a very rare form of bone dysplasia. Otorhinolaryngologically, proper follow-up of these patients and appropriate treatment of upper airway problems are important to achieve an acceptable quality of life. Adeno/adenotonsillectomy and positive pressure ventilation, used as conservative approaches in treating upper airway problems, are effective and could be used instead of an aggressive surgery such as tracheotomy or maxillomandibular advancement. This study, to the best of our knowledge, is the largest ENT case series on pycnodysostosis.